PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN TATA KECANTIKAN RAMBUT DI LKP PROSTYLE KOTA BEKASI - Fadsyah, Dewi; Muis, Abdul; Santika, Tika (Comm-Edu (Community Education Journal), 2025)
This study aims to describe the empowerment of women through hairdressing training in LKP Prostyle Bekasi. This study uses descriptive analysis with a qualitative approach. The subjects of the study were four people, namely LKP managers, instructors and two trainees. Data collection techniques using interview techniques, observation and documentation. Validity of data using source triangulation and triangulation techniques. Data analysis techniques include data collection, reduction, data display, and conclusion. The results explain that the training process is divided into three stages, namely planning, implementation and assessment/evaluation. Planning is determined by setting training goals. Infrastructure facilities adapted to the budget Disdik Bekasi. Recruitment of training instructors is selected directly by the manager and of course competent and recruitment of 20 participants. Implementation of training for 160 hours as many as 40 meetings. The training materials are tailored to the needs of the participants. Media training in the form of modules and salon equipment. The training method uses a semi-private method with a personal approach and an andragogical approach. Assessment/evaluation on hairdressing training at LKP Prostyle is through assessment or national examination from the Professional Certification Body (LSP).